Chieftaincy in Malawi: Reinvention, Re-emergence or Resilience? A Kasungu Case Study. Issue 2 (3rd March 2020) - Power, Joey
Abstract : As African states emerged from colonial rule and adopted the trappings of western parliamentary government, many nationalist politicians regarded chieftaincy as an archaic institution, either to be abandoned or reduced to ceremonial. Nevertheless, it has become clear that chiefs endure and not merely as cultural ornaments; indeed, in Malawi and elsewhere, they are still the main conduits for communication between the central state and the grassroots, and they continue to play an important role in development initiatives, local dispute resolution and, since the 1990s, as players in the 'new democracy', locally and at the national level. This article contributes to investigations into the nature of chieftaincy from precolonial times to the present, using a Malawian example, to ask how far the tenacity of this institution can be attributed to its reinvention, re-emergence or resilience. It examines chieftaincy in one area of Kasungu district in central Malawi from its establishment in the 18 th century through the colonial and post-colonial periods up to the present to explore its nature over time. It concludes that the institution endures through a combination of reinvention, resilience and re-emergence. Chieftaincy survives through invoking tradition and adapting to specific historical circumstances but also by virtue of the personal qualities of officeholders. This case study illustrates the dynamism of chiefly governance.